Fixation strength of four headless compression screws. Issue 10 (October 2016) - Hart, Adam; Harvey, Edward J.; Rabiei, Reza; Barthelat, Francois; Martineau, Paul A.
Highlights: Early mobilization of scaphoid fractures necessitates fixation to resist pull-apart and bending. In this article, the biomechanical fixation of four headless compression screws is tested. Pull-apart force is substantially reduced in osteopenic and osteoporotic bone. The fully threaded Acutrak screws were most resistant to bending forces. Abstract: To promote a quicker return to function, an increasing number of patients are treated with headless screws for acute displaced and even non-displaced scaphoid fractures. Therefore, it is imperative to understand and optimize the biomechanical characteristics of different implants to support the demands of early mobilization. The objective of this study was to evaluate the biomechanical fixation strength of 4 headless compression screws under distracting and bending forces. The Acutrak Standard, Acutrak Mini, Synthes 3.0, and Herbert-Whipple screws were tested using a polyurethane foam scaphoid fracture model. Implants were inserted into the foam blocks across a linear osteotomy. Custom fixtures applied pull-apart and four-point bending forces until implant failure. Pull-apart testing was performed in three different foam densities in order to simulate osteoporotic, osteopenic, and normal bone. The peak pull-apart forces varied significantly between implants and were achieved by (from greatest to least): the Acutrak Standard, Synthes 3.0, Acutrak Mini, and Herbert-Whipple screws. The fully threaded screws (Acutrak) failed at their proximal threads while the shanked screw (Synthes and Herbert Whipple) failed at their distal threads. Similarly, the screws most resistant to bending were (from greatest to least): the Acutrak Standard, Acutrak Mini, Herbert-Whipple, and Synthes. Although the amount of force required for pull-apart failure increased with each increasing simulated bone density (a doubling in density required triple the amount of pull apart force), the mode and sequence of failure was the same. Overall, the fully threaded, conical design of the Acutrak screws demonstrated superior fixation against pull-apart and bending forces than the shanked designs of the Synthes and Herbert-Whipple. We also found a strong relationship between simulated bone density and pull-apart force.